Adaptability to climate change in forestry species: Drought effects on growth and wood anatomy of ponderosa pines growing at different competition levels - Fernandez, Maria Elena (2012)
More stressful conditions are expected due to climatic change in several regions, including Patagonia, South-America. In this region, there are no studies about the impact of severe drought events on growth and wood characteristics of the most planted forestry species, Pinus ponderosa (Doug. ex-Laws). The objective of this study was to quantify the effect of a severe drought event on annual stem growth and functional wood anatomy of pines growing at different plantation densities aiming to understand how management practices can help to increase their adaptability to climate change. Growth magnitude and period, specific hydraulic conductivity, and anatomical traits (early- and latewood proportion, lumen diameter, cell-wall thickness, tracheid length and bordered pit dimensions) were measured in the ring 2008-2009, which was formed during drought conditions. This drought event decreased annual stem growth by 30-38% and 58-65% respect to previous mean growth, in open vs. closed stand trees, respectively, indicating a higher sensitivity of the latter, which is opposite to reports from the same species growing in managed native forests in USA. Some wood anatomical variables did differ in more water stressed trees (lower cell wall thickness of early wood cells and higher proportion of small-lumen cells in latewood), which in turn did not affect wood function (hydraulic conductivity and resistance to implosion). Other anatomical variables (tracheid length, pit dimensions, early- and latewood proportion, lumen diameter of early wood cells) did not differ between tree sizes and plantation density. The results suggest that severe drought affects differentially the amount but not the function and quality of formed wood in ponderosa pine growing at different competition levels.